Bioanalytical method development and validation for the simultaneous estimation of Olanzapine and Samidorphan in rabbit plasma by using HPLC-MS/MS and application to pharmacokinetic study - Rambabu Kantipudi; Sugandha Kumar Pavuluri (SpringerOpen, 2024)
Abstract Background Samidorphan is an opioid antagonist while Olanzapine is an effective medication for schizophrenia and bipolar disorder. A unique and accurate MS/HPLC approach due to simultaneous measurement of Olanzapine and Samidorphan is, therefore, more urgently required. Simultaneous quantification of Olanzapine and Samidorphan in rabbit plasma using HPLC-MS. Using a buffer composed of 1 mL of formic acid in 1 L of water and a mixture of two components, buffer and acetonitrile in a ratio of 50:50 and a flow rate of 1 mL/min at room temperature, we separated compounds on an Inertsil ODS column (250 × 4.6 mm, 5 m). Results Analysis was performed within 8 min over a satisfactory linear concentration range of 2-40 ng/mL for Olanzapine (r 2 = 0.99901 0.024) and 2-40 ng/mL for Samidorphan (r 2 = 0.99927 0.012). The matrix effect recoveries of Olanzapine and Samidorphan at various QC concentration levels were 104.5, 100.51% and 110.36, 99.25%, respectively. The precision and recovery study outcomes fall within the acceptable range. An electrospray ionization source was used to analysis of Olanzapine and Samidorphan at m/z 313.40 → 192.54, m/z 371.45 → 220.61 for Olanzapine and Samidorphan, m/z 316.40 → 237.58, m/z 374.41 → 223.61 for D3 Olanzapine and D3 Samidorphan that were ion pairs of mass analysis. Conclusions Liquid-liquid extraction was used to remove Olanzapine (0.17 mg/kg) and its reference standard (D3-Olanzapine) from rabbit plasma. Both the active compound Samidorphan (0.17 mg/kg) and its reference, D3-samidorphan, were isolated from rabbit plasma. We conducted stability studies to ensure that the medications would remain stable in accordance with USFDA regulations.